Hubungan Tingkat Pengetahuan Calon Pendonor dengan Minat Donor Darah Pada Mahasiswa - Achmad Mulyaone; Sitti Rahbiah Akram; Ririn Feriana Basri (SEHATI: Jurnal Kesehatan, 2025)
Blood donation is an essential humanitarian act that contributes to the healthcare system by ensuring the availability of safe blood for patients in need. However, the participation rate of university students in blood donation remains low, even though they are in the productive age group. This study aimed to determine the relationship between knowledge level and interest in blood donation among students in Makassar. A cross-sectional analytic method was used with a total of 100 respondents selected through purposive sampling. Data were collected using a structured and validated questionnaire, then analyzed using the Chi-square test. The findings showed that 41% of respondents had a high level of knowledge, 26% moderate, and 33% low. Meanwhile, blood donation interest levels were 7% high, 78% moderate, and 15% low. The statistical test revealed a significant relationship between knowledge level and blood donation interest (p=0.026). Higher knowledge levels tend to influence student interest, although other factors such as fear, information access, and social support also contribute. It is concluded that education and outreach programs are needed to increase awareness and build a strong culture of voluntary blood donation among students